A study of infection areas and social assessment findings in Hs (haemorrhagic Septicaemia)-affected buffaloes on Samosir Island, Indonesia - Ginting, Nurzainah; Hasnudi; Yunilas; Mirwandhono, E.; Hellyward, J.; Sulistyowati, E.; Hafid, H.; Samsudin, A. A. (EM International, 2022)
HS case has first been reported on Samosir Island in 1989 which infect almost all buffaloes on the island. To date, number of buffaloes registered in this island is 17,352. The highest buffalo death in 2018 was 189 heads. The situation has gave a negative impact on the livestock farmers since rearing buffaloes bring many benefits to them. HS alternately occurs in the sub-district or several sub-districts at once. In this study, the occurrence of HS were evaluated in order to minimize HS spread and infection. Buffaloes in Samosir Island grazed on large grazing areas in remote land and this area were used by many buffaloes from many villages. The infected buffaloes may transmit the disease to other buffaloes. This has triggered cross HS infection of the buffaloes from different area. Buffaloes that died from HS were not always buried because the soil mixed with rocks made the burial process a bit difficult. Not all buffaloes are vaccinated mainly due to willingness to carry out vaccination, knowledge on vaccination, motivation on raising buffalo by the buffaloes owner and availability of vaccine. The cost of the vaccine is very cheap and some of the vaccine are procured by the government agencies with very limited quantity. The findings of this retrospective study may assist in policy making when saving bufflaoes in future from HS infection.